Penerapan Metode Think Pair and Share dalam Meningkatkan Kemampuan Membaca Wacana Bahasa Inggris di SMAN 1 Purworejo - Eko Hendarto (Arus Jurnal Pendidikan, 2021)
This study aims to improve the students’ competence to comprehend the English discourse by using the Think Pair and Share learning method at SMA Negeri 1 Purworejo, Central Java which includes 1) the implementation of the Think Pair and Share method in learning process, 2) the implementation of the Think Pair and Share method in finding the needed information at the level of low order thinking skills (LOTS) and high order thinking skills (HOTS), 3) the analysis on the progress of the students' competence to comprehend English discourse. The subjects of this study were 36 students of Year 12. This research was carried out in two cycles with the data collection techniques in the form of periodic written assessments, observations and questionnaires. The Research instruments were in the form of tests, teacher journals and questionnaires. With the application of the Think Pair and Share method, learning outcomes in understanding English discourse are stated to increase, which is marked by an increase in the percentage of the students’ mastery learning. The percentage of students’ mastery learning was 66% at the pretest, 72% at the 1st cycle, and 82& at the 2nd cycle. This indicated that the Think Pair and Share method works effectively in improving the participants' ability to read English discourse.